Developing competence in diagnostic palpation: Perspectives from neuroscience and education - Esteves, J; Spence, C (2014)
Palpation plays a central role in osteopathic clinical decision making, yet it is one of the hardest clinical skills to develop, teach, and assess. In fact, it could be argued that osteopaths literally diagnose with most of their senses. Information conveyed by the osteopath's different senses is processed and interpreted in his/her brain, taking into consideration the relevant anatomical, physiological, and pathological knowledge, osteopathic models of care, and the osteopath's own clinical experience. It has been claimed that expert clinicians demonstrate palpatory literacy to the extent that they often speak of having 'listening' or 'seeing' hands. Considering the plastic nature of the human brain, we argue that that the development of palpatory diagnostic expertise is likely to be associated with behavioural, neuroanatomical, and neurophysiological adaptive changes. Building upon the initial findings of our ongoing research examining the neural and behavioural correlates of diagnostic expertise in osteopathy and on evidence from the fields of cognitive neuroscience, experimental psychology, and medical cognition, this paper proposes ways in which the development of competence in diagnostic palpation can be optimised. We propose that as students progress through their programme of study, they should be encouraged to use available opportunities to experience normal and altered patterns of structure and function; and reflect on the validity and reliability of their diagnostic judgements. © 2013 Elsevier Ltd. All rights reserved.